Proses Spasial Permukiman Liar (Squatter) di Sempadan Sungai Wiso di Kecamatan Jepara Tahun 2001-2010 - Anas, Ma’ruf M; Eva, Banowati; Sriyono, Sriyono (Geo-Image, 2018)
Spatial process is a reciprocal relationship between the spatial context, movement and in a certain time perception. Judging from the process, spatial development physically consists of two developmental processes, namely the development process horizontally and vertically. The process of definitive horizontal spatial development can be formulated as a process of horizontally adding space, while vertical development is the addition of space in the interior by building a multi-story building. Settlers residing in the river boundary play a role in the development of wild settlements that occur in the border of the River Wiso, District Jepara. This study aims to (1) Describe the profile of settler households that live in the wild border Wiso River District Jepara. (2) Knowing the cause of the emergence of squatter settlements in the river border Jepara Sub-district. (3) Analyzing the spatial settlement processes that occurred alongside the river of Jepara Regency in 2001-2010. The research method used is observation, interview, questionnaire, documentation, and interpretation of the image from 2001-2010. Population Research is all settlements located in the border of Wiso River in Saripan, Panggang, and Pengkol. This study used saturated sampling as much as 44 respondents. Data analysis using Descriptive Percentage.